Working from Home to Manage Change in Turbulent Times: An Exploratory Study of Work Life Balance among Kenyan Female Employees - Kendagor , Ruth J. (African Journal of Education,Science and Technology (AJEST), 2022)
Working from home is emerging as an avenue for companies to maintain continuity and productivity in this COVID-19 pandemic era. However, the hurried manner of its implementation does not auger well with the multiple roles that women in employment are expected to play juggling work and home. Work life balance has been found to be critical among people in employment yearning to strike a balance between their work and home needs. This study builds on the work life balance philosophy to explore practices that female workers in Kenya leverage to manage the change that is working from home. The study employs an exploratory approach that targets working females drawn from diverse sectors in Uasin Gishu County, Kenya. Due to the infinite nature of the target population, the study used Convenience sampling to sample Ten (10) female workers to participate in the study. Data gathered through semi-structured interviews and, analyzed thematically establishes that female employees in Kenya encounter both positive and negative experiences working at home. Although they get the opportunity to be in control of their work schedule, and lead happier and healthier lives, they are mostly isolated, distracted, and overloaded in their duties. To balance such experiences, they normally resort to prioritizing duties, setting boundaries, and creating time for relaxation.